‘Taking up the Mask of Humanity’: Clement of Alexandria’s Dramatic Understanding of the Two Natures of Christ - Creedy, Edward (The journal of theological studies, 2025)
In the ninth century, Photios of Constantinople accused Clement of Alexandria of promoting a deficient ‘docetic’ Christology in his now-fragmentary Hypotyposes. This provoked a debate that continues to dominate discussion of Clement’s theological understandings—whether his extant christological comments constitute a proto-orthodox position, or reveal the influence of docetism. This paper argues that Photios’ accusations have been something of a red herring, and the subsequent debate has obscured Clement’s actual christological position. His own thoughts are most clearly articulated in chapter 10 of his exhortatory Protrepticus, as Clement presents a christological explanation through the language and metaphor of ancient drama. Christ is described as taking up the mask of humanity and performing the drama of salvation, and Clement leans on a wider contemporary understanding of the relationship between mask (προσωπεῖον) and actor to present this complex doctrine to his readership. Through a focus on this presentation, this paper will offer a solution to a debate that has troubled scholars for over a millennium, and which has blinkered our understanding of Clement’s Christian project more broadly.